Additive manufacturing of Inconel 625 superalloy parts via high pressure cold spray - Bhowmik, Ayan (2018)
Cold gas dynamic spray (CGDS) or simply ‘cold spray’ (CS) is an emerging additive manufacturing technique, which is used in repair applications of metal components. The benefits of CS process are good metallurgical bonding with less heat-affected zone compared to traditional metal joining processes (i.e. welding, thermal spray etc.) or electron beam melting (EBM) or selective laser melting (SLM) additive manufacturing methods. In this study, Inconel 625 was deposited on Inconel 718 substrate via a high pressure cold spray system. The window of deposition for Inconel 625 particles, gas flow and particle acceleration behavior were investigated by numerical simulations. Powder and coating microstructures were investigated by a combination of optical microscopy and scanning electron microscopy. The bond strength between coating and substrate was tested according to ASTM C633. The hardness tests for both the substrate and the as-sprayed coating were conducted. The results showed that the CS Inconel 625 coatings had a low porosity level and an intimate interface. The bond strength between coating and substrate was greater than the maximum epoxy strength. The good quality of the CS Inconel 625 deposits showed a great application potential for the additive manufacturing of Ni-based superalloy parts.